2020
DOI: 10.1002/ange.202010309
|View full text |Cite
|
Sign up to set email alerts
|

Die Natur starker Chalkogenbindungen unter Beteiligung chalkogenhaltiger Heterocyclen

Abstract: Chalkogenbindungen sind Sigma‐Hole‐Wechselwirkungen und kommen seit einiger Zeit als Alternative zu Wasserstoffbrückenbindungen zum Einsatz. In der Regel werden das elektrostatische Potential am Chalkogenatom und Delokalisierungseffekte für die Orientierung der Chalkogenbindung verantwortlich gemacht. Wir konnten jedoch mithilfe von SAPT‐Berechnungen zeigen, dass weder der induktive Term (Delokalisierungseffekte) noch der elektrostatische Term die räumliche Orientierung starker Chalkogenbindungen in tellurhalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Continuing research has revealed the occurrence of these bonds in biomolecules such as proteins and nucleic acids [21,35–39] or SAM riboswitches [36] . The ChB runs a full spectrum of bond strength [40] with Te being particularly strong, [41] and reveals itself in a number of ways including solid state NMR [42,43] . A good deal of our present understanding of the ChB is contained in a number of recent review articles [24,44–48] to which an interested reader is referred.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing research has revealed the occurrence of these bonds in biomolecules such as proteins and nucleic acids [21,35–39] or SAM riboswitches [36] . The ChB runs a full spectrum of bond strength [40] with Te being particularly strong, [41] and reveals itself in a number of ways including solid state NMR [42,43] . A good deal of our present understanding of the ChB is contained in a number of recent review articles [24,44–48] to which an interested reader is referred.…”
Section: Introductionmentioning
confidence: 99%